Cognitive Construction and Meaning Generation of Survival Narratives: Discourse Analysis of Artists in the Songzhuang Art District - Zhao, Chen; Bin Mohd Ali, Noor Azizi; Bin Hasna, Mohd Fabian (Forum for Linguistic Studies, 2025)
The study presented in this paper involves the cognitive construction and sense-making processes of survival narratives among artists in Songzhuang Art District, one of the country's famous art communities located outside of Beijing. This paper is based on a mix of methods of semi-structured interviews (n = 20), participatory observation, and analysis of social media posts by 15 artists to explore how these artists, marginalized by urbanization, commercialization, and societal isolation, use language to form survival narratives. Employing cognitive linguistics and discourse analysis, the paper investigates how identity negotiation, resistance, and self-legitimization are reflected in linguistic structures such as metaphor, framing, and narrative organization. These narratives are not just personal accounts but cognitive tools that help make sense of social conditions. Three overarching themes occur: marginalization, with 90 % of the artists adopting an exclusionary vocabulary to represent their separation with the mainstream market of artworks; resistance, where 35 % of the social media will use language of activism and political action through art; and self-legitimizations, where 40 percent posts indicate linguistic markings on artistic independence and identity crafting. Artists use social media to generate discursive spaces and insist on their legitimacy, fight commercialization and create communities that support them. The paper provides a contribution to the study of how marginalized communities in art employ linguistic and cognitive means to construct and distribute survival narratives, providing fresh information to the studies on the interconnection of art, identity, and resistance to the processes of urbanization and commercialization.